2011
DOI: 10.1007/s00167-011-1509-x
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic autologous chondrocyte implantation in osteochondral lesions of the talus: mid-term T2-mapping MRI evaluation

Abstract: Therapeutic study, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 40 publications
5
47
0
3
Order By: Relevance
“…The 95% percentile value was 50 ms. 4 To analyze the assay results, we averaged the values in each area (88 ROIs). Those above 50 ms, which reveal poor-quality remodeling inflammatory tissue, [31][32][33] were counted to compute the poor cartilage index (PCI, expressed as a % of all values obtained in the 88 ROIs), as described in the Results. Values above 90 ms were not used for computations.…”
Section: Mri Assessmentsmentioning
confidence: 99%
“…The 95% percentile value was 50 ms. 4 To analyze the assay results, we averaged the values in each area (88 ROIs). Those above 50 ms, which reveal poor-quality remodeling inflammatory tissue, [31][32][33] were counted to compute the poor cartilage index (PCI, expressed as a % of all values obtained in the 88 ROIs), as described in the Results. Values above 90 ms were not used for computations.…”
Section: Mri Assessmentsmentioning
confidence: 99%
“…Morphological MRI follow-up, using the Magnetic Resonance Observation of Cartilage Repair Tissue scoring system 73 , revealed integration of the regenerated tissue, as well as subchondral edema in two patients (20%). Battaglia et al recently reported the results of an arthroscopic autologous chondrocyte implantation technique in twenty patients with a mean age of thirty-five years and a mean follow-up duration of five years 74 . The mean AOFAS functional outcome score increased from 59 points preoperatively to 84 points postoperatively, while quantitative T2-mapping evaluation revealed a repair tissue similar to native cartilage covering 69% of the total defect area.…”
Section: Periosteum-covered Techniquementioning
confidence: 99%
“…Entretanto, em situações clínicas, o edema ósseo pode ocorrer pela perda da integridade da cartilagem articular ou contusões articulares, e constitui a expressão de algumas alterações histológicas como fibrose, necrose, hemorragia óssea e micro fraturas trabeculares (Grossi et al 2001, Rodrigues & Camanho 2010, Yusuf et al 2011, Lei et al 2014. De acordo com Battaglia et al (2011), após 5 anos do tratamento de lesão osteocondral no osso talo de humanos, 65% dos pacientes apresentaram edema ósseo subcondral e este achado estava correlacionado com menores porcentagens de tecido de reparação com cartilagem hialina. No atual estudo, acredita-se que o edema ósseo observado ao exame de RM em algumas amostras foi decorrente do processo esperado de reabsorção e remodelação desencadeado pelo tecido enxertado e pelas microfraturas ósseas ocasionadas pela indução do defeito, e não representou uma alteração importante no processo de reparação.…”
Section: Discussionunclassified
“…A partir da utilização de técnicas específicas para a região articular, a RM fornece informações sobre as alterações de sinal do tecido cartilaginoso, da morfologia da superfície articular e do osso subcondral (Rodrigues & Camanho 2010, Kido et al 2014. Além disso, em tratamentos com enxertos osteocondrais, proporciona a obtenção de dados estruturais importantes a respeito do preenchimento do defeito, da integração do tecido de reparação com a cartilagem circundante e do aspecto da superfície articular (Nho et al 2008, Battaglia et al 2011.…”
Section: Introductionunclassified